Peran Guru Terhadap Antisipasi Terjadinya Bullying Di SMP Hangtuah 1 Belawan - Simanullang, Martua Felix Jonatan; Anzalia, Bella Ayu; BR Sembiring, Nike Margaretha; Halimah, Halimah; Purba, Griyani Elisabeth; Purba, Rani Oktavia; Jamaludin, Jamaludin (Pusdikra Publishing, 2024)
Education at school is a structured educational environment that aims to provide knowledge, skills and values ??so that students can develop their potential. Examples of bullying at SMP Hangtuah 1 Belawan include threats, verbal or physical conveyance, name-calling, or spreading false rumors. Bullying can have serious impacts on its victims, including decreased mental well-being, low self-esteem, and psychological problems, and can even end. to acts of despair such as suicide. The role of teachers in anticipating bullying at SMP Hangtuah 1 Belawan is very important. They can do things like create a safe and inclusive environment, provide training to students and staff on bullying awareness, supervise interactions between students, and handle bullying incidents quickly and appropriately. Apart from that, they can also involve parents and the community in efforts to prevent bullying. The research was carried out using qualitative methods, this research was carried out at Hangtuah 1 Belawan School. We conducted interviews with two participants who represented the parties concerned. Data was collected through in-depth interviews lasting between 60-90 minutes. The questions asked include problems that occur at school.